Factors influencing knowledge of hibah among muslims in Alor Setar, Kedah - Nur Syaedah, Kamis (2019)
Hibah is one of the effective tools in Islamic estate planning and management in order to encounter severe economic problems facing in our country such as increasing number of frozen inheritance asset and unclaimed money, abundant uneconomical idle inheritance property and mounting arrears of immovable property tax. These problems demonstrate serious losses to Muslims which opposing the spirit of Maqasid Shari 'ah i.e. to protect the wealth. Indeed, the lack of knowledge in estate planning and management leads to detrimental impacts to Muslims' society and it is alleged that Muslims also lack of knowledge in hibah . Thus, the objectives of this study are to evaluate the level of knowledge of hibah among Muslims in Alor Setar Kedah and to investigate the factors influencing the knowledge of hibah. The data collected for this study is from 195 respondents among Muslims in Alor Setar Kedah , whom answered the questionnaires distributed. The result shows that the level of knowledge of hibah among Muslims in Alor Setar Kedah is at good level and four (4) factors i.e. education stream, religiosity, social influence and social were identified to significantly influencing knowledge of hibah. Hence, several recommendations have been provided in this study to relevant authority and agencies as well as for the future study.